Understanding women's feelings about safety and hazards of street drinking in London through interpretative phenomenological analysis. (December 2019) - Tyler, Allan; Moss, Antony C.; Cox, Sharon
Abstract: Aims: Drinking alcohol in outdoor public places (e.g. streets and parks) and outside of formally organised events is perceived and reported as antisocial behaviour and may be indicative of a problematic relationship with alcohol, and other clinical needs. This paper aims to address a lack of qualitative research on street drinking in the United Kingdom and develop a textured understanding of the lived-experience of how some women engage in street drinking, in the context of one London borough. Method: The authors collected semi-structured interviews as part of a larger mixed methods study on street drinking from April to August 2018. A sub-set of interviews ( n = 3) with women who were accessing local drug and alcohol services and had a history of street drinking behaviour were selected as a case series for triangulating analysis with a smaller, homogenous sample. These data were analysed using Interpretative Phenomenological Analysis with a reflexive, feminist, social constructionist approach. Results: The authors developed and named a superordinate theme, Constellations of Safety and Hazards for Women Drinking in Public and Private. Within this, four themes were defined and illustrated from the data: Drinking outdoors to be away from hazards at home; Women's awareness of geo-temporal factors to moderate risk; Women identifying risks of accepting drinks from strangers; and Threats of untreated trauma within histories of heavy drinking. Definitions and illustrations from participants aid explanations of how the texts add detail or disruption to dominant discourses. Conclusion: The case studies illustrating how these women have experienced alcohol misuse and behaviour change provide reflexive accounts of exercising agency in managing embodied and affective states of vulnerability. This was demonstrated by asserting choice around environmental spaces and friendships, even when still in positions deemed as 'risky'. These three women's decisions around drinking in public, outdoor spaces were shaped by complex interactions of interpersonal, intrapersonal, socio-economic, and cultural structures. Understanding behaviours is improved with data that situates people in contexts where they experience and make sense of their lives. Highlights: Women's narratives add detail and disruption to dominant discourses of street drinking. Women in recovery from alcohol dependence exercise agency to manage various embodied and affective states of vulnerability. Women drinking outdoors may be locating themselves away from dangerous home environments. Women illustrate hierarchies of risks in drinking in public spaces and accepting drinks from strangers. Untreated trauma and perceptions of stigma are salient in women's narratives of street drinking.